PENGARUH PROMOSI DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA DAPUR DEWI KAHYANGAN JOMBANG - Putri Mulya Agustinah; Winaika Irawati (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
This research is to find out how the influence of promotion and price perceptions on purchasing decisions at Dewi Kahyangan Jombang Kitchen. Dewi Kahyangan Kitchen (DK Kitchen) Jombang is a restaurant located in Jombang district, East Java. In addition to serving a number of home cooking menus which can be said to be a general menu, Dewi Kahyangan Jombang Kitchen also serves various menus of processed chicken, duck and seafood which are very suitable to be enjoyed with familyyy, friends and co-workers. All data in this study were obtained from observations, interviews, and distributing questionnaires to direct consumers. This study uses a type of quantitative research using multiple linear regression analysis. The number of samples used is as many as 50 respondents who make transactions/payments at Dewi Kahyangan Jombang's Kitchen with the non-probability sampling method using saturated sampling techniques. Data analysis techniques used validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the analysis show that 1.) promotion has an effect on purchasing decisions. 2.) price perception has a positive and significant effect on purchasing decisions. 3.) Promotion and perceived price together (simultaneously) influence purchasing decisions at Dewi Kahyangan Jombang Kitchen